Physicochemical and electrochemical behaviours of manganese oxide electrodes for supercapacitor application. (April 2020) - devi, Nitika; Goswami, Manoj; Saraf, Mohit; Singh, Bhupendra; Mobin, Shaikh M.; Singh, Rajesh Kumar; Srivastava, A. K.; Kumar, Surender
Highlights: MnO2 nanostructures are prepared by chemical reduction of KMnO4 using different reducing agents. Mn3 O4 in Hausmannite structure formed with MnO2 by using the strong reducing agents (NBH, HH). Morphology of MnO2 changed with reducing agent. Nanowires of MnO2 prepared by using formic acid shows highest capacitance value of 155 Fg −1 at 0.64 Ag −1 . Abstract: Objectives of this study are to probe the effect of reducing agents on physicochemical and electrochemical properties of manganese oxide. Manganese oxide is synthesized by chemical reduction of KMnO4 at room temperature using ethylene glycol, hydrazine hydrate, Na2 S2 O3, potassium iodide, formic acid, citric acid, and NaBH4 . All as-prepared manganese oxide samples are analysed by powder XRD, FE-SEM and FT-IR. It is found that manganese oxide prepared using formic acid and sodium thiosulphate have nanorod or nanowire type morphology as confirmed by FE-SEM analysis. Electrochemical properties of samples are studied in aqueous medium (1 M Na2 SO4 ) by cyclic voltammetry and galvanostatic charge-discharge techniques. Due to the rod type structure formic acid sample shows high surface area (117 m 2 g −1 ) and high porosity (0.1331 cc g −1 ), which results into high specific capacitance of 155 Fg −1 at 0.64 Ag −1 . Graphical abstract: Image, graphical abstract